2019
DOI: 10.1039/c8nj06119j
|View full text |Cite
|
Sign up to set email alerts
|

A morphology-tailored triazine-based crystalline organic polymer for efficient mercury sensing

Abstract: A melamine-based crystalline organic polymer as a highly efficient ultra-trace Hg2+ ion sensor with a detection limit of 0.03 ppb.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…According to the HSAB theory, the soft d-block metal ion Hg 2+ exhibits a strong preference for bonding with soft sulfur-based ligands over nitrogen-based ones . Notably, organic ligands featuring unsaturated nitrogen atoms exhibit a soft Lewis base behavior, facilitating the formation of stable coordination complexes, especially evident in their interactions with soft Lewis acid transition metal ions . Moreover, the formation of weak π bonds between carbon and adjacent nitrogen atoms results in electron density accumulation around the periphery of the nitrogen atoms, augmenting their electron-donating capacity and further supporting their characterization as soft bases. , The larger ionic radius of Hg 2+ ions enables easier polarization and deformation when interacting with the nitrogen atoms of POP CCAD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the HSAB theory, the soft d-block metal ion Hg 2+ exhibits a strong preference for bonding with soft sulfur-based ligands over nitrogen-based ones . Notably, organic ligands featuring unsaturated nitrogen atoms exhibit a soft Lewis base behavior, facilitating the formation of stable coordination complexes, especially evident in their interactions with soft Lewis acid transition metal ions . Moreover, the formation of weak π bonds between carbon and adjacent nitrogen atoms results in electron density accumulation around the periphery of the nitrogen atoms, augmenting their electron-donating capacity and further supporting their characterization as soft bases. , The larger ionic radius of Hg 2+ ions enables easier polarization and deformation when interacting with the nitrogen atoms of POP CCAD.…”
Section: Resultsmentioning
confidence: 99%
“…28 Moreover, the formation of weak π bonds between carbon and adjacent nitrogen atoms results in electron density accumulation around the periphery of the nitrogen atoms, augmenting their electrondonating capacity and further supporting their characterization as soft bases. 29,28 The larger ionic radius of Hg 2+ ions enables easier polarization and deformation when interacting with the nitrogen atoms of POP CCAD. The high selectivity of the POP CCAD for Hg 2+ ions may be ascribed to its faster chelating process with the nitrogen sites.…”
Section: ■ Experimental Sectionmentioning
confidence: 92%
“…In order to describe the kinetics of mercury ion adsorption, we use a pseudo-second-order model to fit the data, which is represented by eq : …”
Section: Resultsmentioning
confidence: 99%
“…In order to describe the kinetics of mercury ion adsorption, we use a pseudo-second-order model to fit the data, 38 which is represented by eq 4: In the formula, k 2 (g mg −1 min −1 ) is the quasi-secondary adsorption rate constant, q t (mg g −1 ) is the amount of Hg (II) adsorbed at time t (min), and q e (mg g −1 ) is the amount of Hg(II) adsorbed at equilibrium. By calculating the above adsorption data for Hg(II), we observed that the rapid kinetic rate k 2 = 16.5 g mg −1 min −1 , a very high correlation coefficient (R 2 = 0.9994) (Figure 8a).…”
Section: ■ Results and Discussionmentioning
confidence: 99%